Thinking about education in a prefigurative key. Challenges and contributions to social thought from the pedagogical praxis of social and popular movements - Sánchez Pacheco, Rosa Margarita (2024)
The crisol of educational experiences in Latin America is diverse and vast, weaving processes from a popular, liberating, critical, bottom up, communal approach. From there, many continue to open paths and possibilities in the region; in this journey, social and popular movements propose coordinates for us to think and act in the educational field in its multiple dimensions and possibilities. From there, it is possible to recognize a commitment in which pedagogical experiences already configure (prefigure) the bases of liberation processes. Along this route, the objective of this work is to propose a recovery of the political-pedagogical praxis of popular and/or social movements based on the notion of prefigurative politics. From there, we could identify some features to recognize contributions and challenges to pedagogical thinking and sociology to think and act from education in a prefigurative key.